Penentuan Kandungan Fenolik Total Kombinasi Ekstrak Etanol Daun Jeruk Purut (Citrus hystrix) Dan Daun Kelor (Moringa oleifera L.) : Determination of Total Phenolic Content in Combination Ethanol Extracts of Kaffir Lime Leaves (Citrus hystrix) and Moringa Leaves (Moringa oleifera L.) - Fadilah Qonitah; Reni Ariastuti; Jihan Aulia Kusumasari (Jurnal Sains dan Kesehatan, 2023)
Kaffir lime leaves and moringa leaves are known to contain phenolic compounds that can have potential as antioxidants. The purpose of this study was to determine the total phenolic content of the combination of ethanol extracts of kaffir lime leaves and moringa leaves. Preparation of extracts was done by maceration method using 95% ethanol. Determination of total phenolic content by colorimetric method using Folin-Ciocalteu reagent and gallic acid as standard. The results showed that the largest total phenolic content in the combination of J:K extract (1:0) was 3.58 ± 0.09 %EAG while the smallest phenolic content in the combination of J:K extract (0:1) was 1.32 ± 0.08 %EAG.